THE FAMILY AS A FACTOR IN THE INTEGRAL DEVELOPMENT OF PRESCHOOL CHILDREN - Radovan Čokorilo; Grk Milana (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Starting from the idea of organic unity between mind and body, the interdependence of organism and environment, and the contribution of physical activity, social, emotional and physiological development today is more correct to speak of "education through the physical" than the "physical education". According to this understanding of physical education is turning into a rich activity that not only develop muscles and coordination of movements, but as a whole person - physical education is becoming the backbone of global development. On the other hand, the family is an important factor in physical education because it formed the first paragraph and the first knowledge of the importance and value of physical education. Here is a very important role of parents as well as socio-economic status of families and family circumstances which manifests as a braking or promotion of child development. It is known that children from families that have a negative attitude towards sport and physical culture in general, are usually not involved in any sport or recreational activity. Many parents do not realize the importance of physical education and physical activity for proper development of the child or at least not sufficiently aware of that importance. Therefore they are very poorly or not at all interested in the results that their children achieve in sport and physical education has a negative effect on their further development. The paper analyzes the external factors of physical development and motor skills, especially the influence of family circumstances. The aim of this paper is that analysis of previous research in this field point out the good results and pedagogical implications of established knowledge but also to the synthesis of these findings point to possible practical solutions to defined problems.